Estimating abundance in unmarked populations of Golden Eagle ... - Stien, Jennifer; Audun, Stien; Tveraa, Torkild; Rød-Eriksen, Lars; Eide, Nina (Dryad, 2022)
1. Estimates of species abundance are of key importance in population and ecosystem level research but can be hard to obtain. Study designs using camera-traps are increasingly being used for large-scale monitoring of species that are elusive and/or occur naturally at low densities. 2. Golden eagle (Aquila chrysaetos) is one such species, and we investigate whether existing large-scale monitoring programs using baited camera-traps can be used to estimate the abundance of golden eagles, as an alternative to traditional labour-intensive searches for active territories and nest sites during the breeding period. 3. The camera-trap data allowed two measures of abundance to be estimated within each of four main study areas in mid and northern Norway; occupancy was measured as the probability of camera site use, and population size was measured as the number of eagle individuals using the camera sites within a study area. Spatial and temporal patterns in occupancy and population size were explored and evaluated ... : The data used were obtained from two regional research projects in Norway targeted towards the conservation of the nationally endangered arctic fox (Vulpes lagopus). Both projects use baited camera-traps (RECONYX©) during late winter with the primary goal to monitor arctic fox abundances as well as other potentially competitive species in the scavenger community, including golden eagles. Data from the COAT monitoring program originates from the north-eastern part of Finnmark County (70 ° N and 26 – 30 ° E) and data from the second monitoring program originates from three areas in mid-Norway, Dovrefjell (62°22′ N 95 and 9°03′ E), Sylan-Forollhogna (63°00′ N and 12°09′ E) and Børgefjell (65°15′ and 13°46′). Please see the published article for details regarding how the datasets were processed. ...